HYGIENE DAN SANITASI USAHA SALON KECANTIKAN DI KOTA PADANG PANJANG - Sulvita, Robby; Rostamailis, Rostamailis; Minerva, Prima (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The background of this researchis about the lack of awareness of the beauty salon employees in considering the aspects related to surveillance efforts on health, both individuals and neighborhood beauty salon. The study purposees were to analyze on Hygiene and Sanitation beauty salon business with Primary category in Padang Panjang City include Personal Hygiene and Sanitation beauty salon environment. Researchtype is quantitative descriptive. Research population is the whole beauty salon in Padang Panjang City, amounting to 10 salons with the number of employees 48 people. Samples of the study were the leader / employee beauty salon in Primary category totaling 30 people with purposive sampling technique. The technique of collecting data using questionnaires and observation are arranged according to a Likert scale and Guttman scale which has proven its validity and reliability. Based on the analysis of Hygiene and Sanitation beauty salon business in Padang Panjang City with indicators; 1) Personal Hygiene in fairly goodcategory (10%), with sub-indicators, namely; a) Maintenance of cleanliness infairly goodcategory (47%), b) Maintenance of cleanliness in very good category (77%). 2) Sanitation neighborhood beauty salon located in fairly good category (27%). The sub-indicators, namely; a) Eligibility beauty salon building in poorly category (7%), b) Quality of water in very good category (60%), c) Waste management is classified in good enough category (0%), d) Control of waste classified in good enough category (9%), e) Health tools and cosmetics materials in quite good category (0%). So, unknown Personal Hygiene and Sanitation beauty salon environment as a whole is still not maximize. Keywords: Hygiene, Sanitation, Beauty Salon Business